Exploring the Benefit of Introducing Accounting and Finance Knowledge for Micro and Small Entrepreneurs During the COVID-19 Pandemic - Hidayah, Nurul; Nugroho, Lucky; Suharman, Harry; Ali, Anees Janee (UI Scholars Hub, 2022)
This study aims to explore the benefit of introducing the accounting and finance knowledge for micro and small business enterprises, in particular during the time of the coronavirus disease 2019. The COVID-19 pandemic has severely affected the micro and small enterprises. A large number of industries faced the risk of lower sales, which in turn badly hit their businesses. To assist micro and small business entrepreneurs in maintaining sustainability by improving their bookkeeping skills by using digital applications, a team of lecturers from Universitas Mercu Buana, Indonesia, and Universiti Sains Malaysia, Malaysia, collaborated on socialization activities and interactions. The lecturers held virtual or online workshops for 75 micro and small business entrepreneurs, whose majority of the participants have a high school educational background. The results of this study show influential benefits experienced by the participants, who also stated that the activity and social interaction must be held regularly as a guide and to provide them with updated information. The activities also motivated them to continue working hard to sustain their business. This study demonstrates that such programs can provide support for the sustenance of micro and small businesses.